2011
DOI: 10.1016/j.jcrs.2010.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fixed brimonidine–timolol combination on intraocular pressure after phacoemulsification

Abstract: The fixed brimonidine-timolol combination effectively reduced IOP 6, 12, and 24 hours after phacoemulsification cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…The use of topical IOP-lowering agents (brimonidine, timolol, and carbonic anhydrase inhibitors), singly and in combination form, and oral antihypertensive agents (acetazolamide) both preoperatively and postoperatively to control early postoperative IOP elevation after cataract surgery has been demonstrated in several previous studies. 12,[25][26][27] In addition, the use of intracameral carbachol and acetylcholine after completion of cataract surgery has also proven useful in controlling early postoperative IOP elevation. 28,29 The results of our study suggest that the use of these agents might be advisable in resident-performed surgeries, especially those with risk factors associated with a high likelihood of significant IOP elevation acutely after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of topical IOP-lowering agents (brimonidine, timolol, and carbonic anhydrase inhibitors), singly and in combination form, and oral antihypertensive agents (acetazolamide) both preoperatively and postoperatively to control early postoperative IOP elevation after cataract surgery has been demonstrated in several previous studies. 12,[25][26][27] In addition, the use of intracameral carbachol and acetylcholine after completion of cataract surgery has also proven useful in controlling early postoperative IOP elevation. 28,29 The results of our study suggest that the use of these agents might be advisable in resident-performed surgeries, especially those with risk factors associated with a high likelihood of significant IOP elevation acutely after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10][11] Although transient IOP elevation is generally well tolerated, eyes with impaired vascular supply may be at increased risk of retinal vascular occlusion or anterior ischemic optic neuropathy, and those with significant preexisting glaucoma risk progressive glaucomatous optic neuropathy. 2,[5][6][7][12][13][14] Previous studies have examined the risk factors associated with early postoperative IOP elevation-most notably preexisting glaucoma and ocular hypertension (HTN) 3,13,15-19 -although longer axial length has been described as well. 20 The effect of surgeon experience on many postoperative complications such as vitreous loss 21 has been examined but data regarding early postoperative IOP elevation have been mixed.…”
mentioning
confidence: 99%
“…Visthesia was used in eleven (10.5%) cases. Seventeen (16%) cases were performed entirely (16) or part-performed (1) by a trainee surgeon supervised by the same consultant surgeon who performed the remaining cases. Ninety-six (90%) of cases were performed under local anaesthesia with the remainder under general anaesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…1,4 The problem with the vast majority of the studies that have investigated prophylaxis regimes for a raised IOP is that they have excluded patients suffering with glaucoma or OHT. [8][9][10][11][12][13][14][15][16][17][18][19] It is of importance to study such regimes specifically in glaucoma and OHT populations, as it is these patients who are most at risk of a raised IOP. 6,12,20 It has been suggested that this pressure rise may be transient postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the earlier data, many surgeons use ocular topical or systemic hypotensive drugs prophylactically before or after cataract surgery to minimize any IOP spikes, albeit there are no specific guidelines. Several studies have been conducted in order to evaluate the efficacy of a variety of antiglaucoma agents on IOP after phacoemulsification . Recently, a brinzolamide‐timolol fixed combination (Azarga, Alcon Pharma GmbH, Puurs, Belgium) has become commercially available and has been approved in the European Union for the treatment of primary open‐angle glaucoma or ocular hypertension.…”
Section: Introductionmentioning
confidence: 99%